Degradation of reactive red 195 by selected bacteria from textile wastewater - Nawahwi, Mohd. Zaini (2009)
Four selected bacterial strains coded R1, R2, Rc and Rd were successfully isolated from raw textile wastewater. They were screened for their ability to degrade an azo dye of Reactive Red 195 on solid and in liquid dye-containing media. Screening showed that decolourization was best performed under anaerobic condition with the highest colour removal (˜70%) showed by bacterium R2. The partial 16S ribosomal ribonucleic acid (16S rRNA) sequence of bacterium R2 shared 98% sequence similarity to Paenibacillus sp.. Decolourization by this bacterium in a chemically defined medium containing (gL-1) of glucose (1), NH4Cl (0.5), K2HPO4 (7), KH2PO4 (2), MgSO4.7H2O (0.1), CaCl2 (0.02), and Reactive red 195 (0.1), adjusted to pH7 and with (10% v/v) inoculum occurred under partial anaerobic condition at temperature of 37°C. Under optimized condition, bacterium R2 successfully removed more than 95% colour and up to 50% of total organic carbon. No significant change in pH was observed (pH from 7.21 to 7.25) though the anaerobiosis was found to be developed throughout the experiment (redox potential reduced from 2.5 to 0.5 mV). This bacterium produced intracellular (0.033 U/mL) and extracellular (0.026 U/mL) azoreductase enzymes which were found to be stable at pH from 6 to 8 and temperature ranging from 30 ºC to 40ºC. High performance liquid chromatography analysis revealed that biodegradation of Reactive Red 195 under partial anaerobic condition produced at least three types of sulfonated amines which were 4-aminobenzenesulphonic acid (sulphanilic acid), 4-amino-3- hydronapthalenesulphonic acid and 4-amino-5-hydronapthalene-2,7disulphonic acid. The sulphanilic acid can be further degraded to a-ketoglutaric acid, a common Krebs cycle’s intermediate in most aerobic microorganism. Therefore, it can be concluded that the Paenibacillus sp. is of good potential use for the treatment of azo dye-containing wastewater based on its ability to remove colour.